Access to crop digital information and the sharing of benefits derived from its use: background and perspectives - Wettberg, Eric von; Khoury, Colin K. (Wiley, 2020)
Crop diversity remains as valuable to global food security as ever. Yet information about this diversity seems to have become nearly as important as the seeds themselves. With the advent of high-throughput DNA sequencing technologies and emerging “phenomic” approaches, and new platforms to store and explore the data they generate, the ways in which our global community can produce and access this information, and share the benefits of its use, is rapidly changing, creating a set of challenges that we will explore in a special collection of papers in Plants, People, Planet. During the 900-day siege of Leningrad from 1942 to 1944, eleven staff members of the Soviet genebank for crop plants and their wild relatives, the All-Union Institute of Plant Industry (now known as the N.I. Vavilov Institute for Plant Genetic Resources or the VIR, after its most famous leader), starved to death protecting its invaluable holdings (Alexanyan & Krivchenko, 1991; Loskutov, 1999). These researchers gave their lives to preserve diversity in crops—from wheat to potatoes, apples to flax—as well as all the information that the scientists had learned about them over the years. They understood the critical importance of the seeds, tubers, and buds, and also the data about their useful characteristics, to the future development of the Soviet State and to global agriculture. They hoped that the coming generations would be able to access these biological materials and associated information, and thus share in the benefits derived from their use. Three quarters of a century later, crop diversity remains as valuable to global food security as ever. Yet the information about this diversity seems to have become nearly as important as the seeds themselves. With the advent of high-throughput DNA sequencing technologies and emerging “phenomic” approaches, and new platforms to store and explore the data they generate, the ways in which our global community can produce and access this information, and share the benefits of its use, is rapidly changing, creating a set of challenges that we will explore in a special collection of papers in Plants, People, Planet. N.I. Vavilov had a vision for the potential of crop diversity to improve agricultural production. After devastating famines experienced in 1919–1921—caused by poor weather and farm collectivization—restoring farm productivity was essential in the Soviet Union. The genetic resource collections compiled between the two World Wars by Vavilov and his colleagues included crop traits such as early maturity, cold hardiness, and disease resistance. These invaluable resources enabled the expansion of cereal, legume, oilseed, fiber, timber, fruit, and vegetable crops over much broader areas of the Soviet Union than previously possible (Dzyubenko, 2018). Similar trends were happening around the world (e.g., Reitz & Salmon, 1968; Salvi, Porfiri, & Ceccarelli, 2013). During and following the Second World War, Norman Borlaug, the Green Revolution pioneer, was able to mobilize crop diversity to develop dwarf stature, disease resistance, and absence of seasonal cues to breed higher yielding wheats in Mexico (Borlaug, 2002, 2007; Swaminathan, 2009) while M.S. Swaminathan and other colleagues adapted these techniques and technologies for expansion into India and beyond (e.g., Swaminathan, 2006). Today's genebanks are essential to maintaining the resilience of the global agricultural system in the face of climate change, new pests and diseases, shifts in trade and dietary preferences, natural resource limitations, and armed conflicts (Figure 1). The recent loss of access to the International Center for Agricultural Research in the Dry Areas (ICARDA) genebank collections in Aleppo, Syria, in the midst of the Syrian civil war—accessions which were thankfully duplicated at sister international genebanks and at the Svalbard Global Seed Vault—demonstrates the need for continued international collaborations to safeguard these resources for the long-term. These ex situ conservation systems can only fulfill their full intended roles if researchers, educators, plant breeders, and ultimately farmers and the consumers of their produce have access to these resources. Furthermore, access is increasingly dependent on equitable sharing of the benefits derived from the use of crop diversity with their custodians. The seeds held by the VIR during the Second World War, as well as those in similar genebanks in other industrialized nations, were initially collected from farms and marketplaces without officially mandated benefit to the communities from whom they were originally gathered. Many of the approximately 325,000 accessions collected by Vavilov and his colleagues were obtained from areas then ruled as colonies of European nations. Even after independence came to these areas after the War, further collections built by national genebanks and the international system such as the Consultative Group for International Agricultural Research (CGIAR) through the early 1990s were generally made without globally coordinated agreements regarding benefit sharing. Since the Convention on Biological Diversity (CBD) was established in 1992, the international community has enacted legally binding arrangements to provide access to and share benefits derived from the use of crop diversity. Through the 2004 International Treaty on Plant Genetic Resources (ITPGRFA), which is aligned with the CBD, and the CBD’s own 2010 Nagoya Protocol, mechanisms for access and benefit sharing (ABS) of seeds and other reproductive propagules have been more carefully formalized. With the advent of increasingly powerful information-generating technologies applicable to the exploration of plant genetic resources, including DNA sequencing, gene editing, genomic selection, and high-throughput phenomic characterization, our capacity to understand potentially useful variation and to incorporate it into cultivars has grown (e.g., Arora & Narula, 2017; Crossa et al., 2017; Mir, Reynolds, Pinto, Khan, & Bhat, 2019) (Figure 2). Because these technologies are potentially so transformative, the information they generate has been proposed to be included as part of international access and benefit sharing mechanisms (e.g., Aubry, 2019). As an extreme case, one could imagine that these “game changing” technologies may make crop improvement programs less reliant on the actual biological propagules, that is, the seeds, tubers, and buds, in turn lessening the benefits achieved through mechanisms covering exchange of these physical resources. International debates around including genetic sequence and phenotypic information in the ABS mechanisms of the Nagoya Protocol and the ITPGRFA could have significant impacts on the international flow of information relevant to plant breeding and the conservation of crop genetic resources. Many of these data are currently held in open access formats (Laird et al., 2020). International negotiations on access and benefit sharing of such data have the potential to create increased benefit sharing deriving from their use, but also may hinder important research and dissemination of results. These issues are complex. We believe that creating a forum to highlight the science underlying these technologies and to encourage discussions based on a range of informed opinions on access and benefits surrounding these tools, will make for more productive debates. Ultimately, we hope for international agreements that are effective in their encouragement of equitable sharing of the benefits of plant genetic resources essential to maintaining the productivity, resilience, and nutritional quality of culturally desirably food, fiber, and fuel, in the face of climate change. And from this, there should arise a more accessible global system of conservation and use of crop diversity and associated information, for the benefit of all.